Вариабельность форм и числа брыжеечных лимфатических узлов у кошки домашней (Felis domestica L.) - Беспалова, Л.С. (Вестник зоологии, 1974)
Variability of regional lymph glands of small intestine in Felis domestica L. is manifested outwardly in peculiarities of their forms, number, size, topography (relation to mesentery serous layers, basic and sometimes-segmentary nervo-vascular bundles) as well as in peculiarities of connections (by means of afferent lymph vessels) with the whole organ or its parts. The latter circumstance depends on the glands number which varies from one to seven. Wide individual variability in form of a gland (glands) depends on form, direction, interrelation and degree of expressiveness of boundaries dividing its tissue into separate lobes. Individual variability in a number and form of mesenteric lymph glands is considered as one of manifestations of peculiarity of their phylo - ontogeny - formation of numerous glands on the base of primarily common one.